Real Clinical Effectiveness of Molnupiravir Against 30-day Mortality Among 74 541 SARS-CoV-2-Positive Patients: A Nationwide Cohort Study From the Czech Republic - Pavlík, Tomáš; Jarkovský, Jiří; Šanca, Ondřej; Koziar Vašáková, Martina; Dlouhý, Pavel; Černý, Vladimír; Štourač, Petr; Válek, Vlastimil; Dušek, Ladislav (Open forum infectious diseases, 2024)
BACKGROUND: We examined the clinical effectiveness of molnupiravir in reducing deaths in a real-world cohort of adult patients with COVID-19 during the Omicron outbreak. METHODS: This was a population-wide retrospective cohort study in the Czech Republic. We analyzed all 74 541 patients with an officially registered diagnosis of SARS-CoV-2 infection between 1 January and 31 December 2022, aged 18 years or older, treated with molnupiravir. The primary outcome was 30-day all-cause mortality; the secondary outcome was 30-day COVID-19-related mortality. Hazard ratios (HRs) were estimated using stratified Cox regression and the Fine-Gray model. RESULTS: The use of molnupiravir in adult SARS-CoV-2 positive patients was associated with a lower risk of both 30-day all-cause mortality: adjusted HR 0.58 (95% confidence interval, 0.53-0.64; P < .001) and 30-day COVID-19-related mortality: adjusted HR 0.50 (95% confidence interval, 0.42-0.58; P < .001). The effect of molnupiravir was highly significant regardless of sex, Deyo-Charlson Comorbidity Index score, hospitalization status, COVID-19 vaccination status, and patients older than age 65 years. CONCLUSIONS: In this cohort study, early initiation of molnupiravir was associated with a significant reduction in 30-day all-cause and COVID-19-related mortality in adult SARS-CoV-2 positive patients.
Keywords: COVID-19-related mortality; SARS-CoV-2 infection; 30-day all-cause mortality; COVID-19; molnupiravir